Pengaruh Persepsi Pendapatan Orang Tua Terhadap Minat Siswa SMA Melanjutkan Perguruan Tinggi Pada Sekolah Swasta Kecamatan Sukoharjo - Ummaya Lathifa Hasna; Mintasih Indriayu; Sudarno Sudarno (Journal on Education, 2023)
The low level of sustainability of high school students to continue their further studies to college is one of the problems in the environment of education. The influence of family economic conditions is one of the factors that can influence students' interest in continuing their studies. This study aims to determine the effect of perceived parental income on high school students' interest in continuing to higher education at private schools in Sukoharjo District. The approach used in this research is quantitative-descriptive. The study population was all class XII students at SMA Veteran 1 Sukoharjo and SMA Muhammadiyah 1 Sukoharjo. The sampling technique is proportionate random sampling, and the total sample was 130 respondents. The primary data source used is the result of distributing questionnaires. Test the validity of the instrument using the Pearson Product Moment and test the reliability with the Cronbach Alpha test. The hypothesis was tested using a linear regression test. The results showed that perceived parental income has a positive and significant effect on the interest of high school students in continuing to college, which was evidenced by the results of a t count > t table (2.991 > 1.657), with a significant effect of 6.4%. Based on the results of the research, the importance of career development and the provision of information about tertiary institutions is needed, especially in terms of educational costs